Tindak Tutur Direktif Guru dalam Pembelajaran Bahasa Indonesia di Kelas VIII SMP - Putry, Chairany Annisa; Arief, Ermawati (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2024)
This research aims to describe directive speech acts, speaking strategies, and the propriety of directive speech acts with the politeness strategies used by class VIII teachers at SMP Muhammadiyah 6 Padang. This type of research is qualitative research using descriptive methods. The data used in this research is the teacher’s utterances during the learning process in class VIII SMP Muhammadiyah 6 Padang. The data source for this research is the Indonesian language teachers. The researcher is the instrument of this research. The data collection techniques for this research are the non-participant observational and note-taking techniques. The research results concluded that there were six teacher directive speech acts in learning in class VIII SMP Muhammadiyah 6 Padang. The dominant speech acts teachers use are asking with 135 data and ordering with 52. There are five politeness strategies used. The dominant strategy is bald on record in 176 data. However, the research results also show a mismatch between the form of directive speech acts teachers use and the politeness strategies applied. A total of 41 pieces of data were found that showed this discrepancy.